2020
DOI: 10.1080/17518253.2020.1741694
|View full text |Cite
|
Sign up to set email alerts
|

Green chemistry approach to the synthesis of 3-substituted-quinazolin-4(3H)-ones and 2-methyl-3-substituted-quinazolin-4(3H)-ones and biological evaluation

Abstract: Teuta Opačak-Bernardi (2020) Green chemistry approach to the synthesis of 3-substitutedquinazolin-4(3H)-ones and 2-methyl-3-substituted-quinazolin-4(3H)-ones and biological evaluation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…59 Also, it has been shown that L-(+)-Tartaric acid and N, N'-Dimethylurea (DMU) as a DES have a significant impact on the yield of quinazolinone synthesis. 60 Similarly, Komar et al 61 have conducted a research on the synthesis of 3-Substituted-quinazolin-4(3H)-ones using ChCl:urea and their results have indicated that DES can be a convenient solvent for this type of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…59 Also, it has been shown that L-(+)-Tartaric acid and N, N'-Dimethylurea (DMU) as a DES have a significant impact on the yield of quinazolinone synthesis. 60 Similarly, Komar et al 61 have conducted a research on the synthesis of 3-Substituted-quinazolin-4(3H)-ones using ChCl:urea and their results have indicated that DES can be a convenient solvent for this type of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Choline chloride-based DESs have been in focus of our investigation for some time, and we found them to be suitable for different chemical processes, both heterocyclic compounds synthesis [17,25,33,43] and extraction [44]. In this regard, the objectives of this research were focused on the investigation on finding an appropriate Type III [36], choline chloride-based deep eutectic (ChCl-based DES) solvent for the synthesis of 3-substituted 2-mercaptoquinazolin-4(3H)-one derivatives, as well as on the influence of some reaction parameters such as temperature and reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…There are many different methods for preparing these extensively studied heterocyclic compounds. Among them, the main synthetic routes use anthranilic acid [15][16][17][18][19], anthranilate [20], isatoic anhydride [21][22][23], benzoxazinone [24][25][26][27] and 2-iodoaniline [28] as convenient precursors. For preparation of 2-mercaptoquinazolinone derivatives, anthranilic acid is the most common starting material.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 3-substituted-quinazolin-4(3H)-one derivatives were prepared by Kom et al [47], using ChCl/urea eutectic solvent, in a two-step cyclization reacti Quinazolinones are a class of six-membered heterocycles exhibiting a range significant pharmacological properties, including antitumor activities [48]. In particu for the synthesis of 2-methyl-3-substituted-quinazolin-4(3H)-ones 62, at first, preparation of benzoxazinone 61, as an intermediate, starting from anthranilic acid and acetic anhydride, was carried out.…”
Section: For Peer Review 12 Omentioning
confidence: 99%
“…Afterwards, benzoxazinone 61 and a prim amine were added to the ChCl-based DES, affording, under heating at 80 °C, corresponding benzo-fused derivatives 62 in 53-84% yield (Scheme 20). A dual role the DES, as both the green medium and catalyst, through the formation of hydrog bonds with the reactants and reaction intermediates, was hypothesized [47]. Moreover, 3-substituted-quinazolin-4(3H)-one derivatives were prepared by Komar et al [47], using ChCl/urea eutectic solvent, in a two-step cyclization reaction.…”
Section: For Peer Review 12 Omentioning
confidence: 99%